Experimental study on pressure field of combined well pattern by water flooding - Wang, Shidong; Xu, Zijian; Pan, Yi; Liu, Hai; Yang, Shuangchun (Kuwait Journal of Science, 2018)
Pressure field variation was investigated using 3D physical equipment. A vertical well was chosen as injector and two horizontal wells were chosen as producers. Pressure point in reservoir were measured by pressure sensors and the pressure distribution image was generated by interpolation. The pressure field was divided into four stages: the forming pressure field stage (I), the stable pressure field stage (II), the decay pressure field stage (III) and the exhaustion pressure field stage (IV). It can be concluded that the decay pressure field stage is the main stage of oil production, and the stable pressure field stage is the most efficient stage.